2020
DOI: 10.33545/surgery.2020.v4.i2d.425
|View full text |Cite
|
Sign up to set email alerts
|

Role of post auricular flaps in acquired partial external auricular defects

Abstract: Background: Reconstruction of acquired partial external auricular defects is one of the most challenging procedures in plastic surgery. Acquired segmental defects of the external ear may be due to trauma, burn, previous surgery, or infection. Aim: The aim of this study is to review the surgical method, its area of application, as well as advantages and pitfalls of reconstruction of the external ear with post auricular flaps. Materials and Methods: 24 patients with acquired partial defects of external ear were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Similar to Dr Shameem Ahamed, who described a total of 45 cases with ear defects, with bulk of cases within 20-50 years [6]. In comparison to Ravikumar Gopalakrishnan, who studied 24 cases of acquired partial auricular defect and most of the cases were 31-40 years, this study showed slight shift of age group to younger population [7].…”
Section: Discussionsupporting
confidence: 62%
“…Similar to Dr Shameem Ahamed, who described a total of 45 cases with ear defects, with bulk of cases within 20-50 years [6]. In comparison to Ravikumar Gopalakrishnan, who studied 24 cases of acquired partial auricular defect and most of the cases were 31-40 years, this study showed slight shift of age group to younger population [7].…”
Section: Discussionsupporting
confidence: 62%